Multiple electron & phonon scattering effect achieves highly efficient thermoelectricity due to nanostructuring. (April 2023) - Hwang, Junphil; Yun, Jae Hyun; Lee, Kwan Young; Rhyee, Jong-Soo; Kim, Jungwon; Acharya, Somnath; Kim, Jiyong; Kim, Woochul; Kim, Sujin; Kim, Sung-Jin
Abstract: To enhance the thermoelectric efficiency of a material, the decoupling of transport parameters in the dimensionless figure of merit, zT is important. The SnTe with MnTe magnetic nanoprecipitates was synthesized resulting in a high figure of merit. The gigantic localized spin moment of MnTe nanoprecipitates effectively scatters the conduction electron in SnTe, decoupling Seebeck coefficient, S, and electrical conductivity, σ . As a result, the powerfactor, S 2 σ was enhanced dramatically over the entire temperature range. The localized spin moment of MnTe nanoprecipitates was significantly larger than that of conventional magnetic atomic substitution in the alloy. Therefore, the spin moment fluctuation of superparamagnetic nanoprecipitates could effectively scatter electrons even at a high temperature. The first quantitative theoretical analysis for electron scattering was conducted in this work, to verify the spin dependent scattering. The weak localization measurement also supported the enhanced electron scattering by localized spin moment. The coherent MnTe nanoprecipitates in the SnTe matrix also reduced lattice thermal conductivity significantly. The slight difference in the lattice parameter between matrix SnTe and precipitates MnTe induced lattice strain and enhanced phonon scattering. The thermoelectric figure of merit zT was recorded 1.8 at 923 K in the eco-friendly material.